2019
DOI: 10.14710/buloma.v8i1.21974
|View full text |Cite
|
Sign up to set email alerts
|

Komposisi Dan Kelimpahan Fitoplankton Di Laguna Segara Anakan, Cilacap

Abstract: Segara Anakan merupakan laguna yang terletak di selatan Pulau Jawa tepatnya di perbatasan antara Jawa Barat dengan Jawa Tengah. Kawasan Segara Anakan merupakan tempat bertemunya sungai besar, sehingga mengalami perubahan penurunan kualitas perairan berupa penyempitan dan pedangkalan akibat proses sedimentasi yang tinggi. Hal ini dikhawatirkan dapat mengakibatkan menurunnya kualitas perairan yang dapat mengganggu pertumbuhan fitoplankton di perairan. Fitoplankton merupakan parameter biologi yang dapat dijadikan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 0 publications
0
18
1
14
Order By: Relevance
“…The highest abundance is station 9 with abundance 6,406 ind L -1 , while station 8 with the smallest abundance with value is 524 ind L -1 . Plankton abundance in Donan river is relatively low compared to Wiyarsih (2019) research which has abundance 29,888 ind L -1 (Table 2).…”
Section: Plankton Abundance and Diversity In The Donnan Rivermentioning
confidence: 74%
See 1 more Smart Citation
“…The highest abundance is station 9 with abundance 6,406 ind L -1 , while station 8 with the smallest abundance with value is 524 ind L -1 . Plankton abundance in Donan river is relatively low compared to Wiyarsih (2019) research which has abundance 29,888 ind L -1 (Table 2).…”
Section: Plankton Abundance and Diversity In The Donnan Rivermentioning
confidence: 74%
“…The results of the research showed that Donan river had 15 plankton genera divided into 10 genus of phytoplankton and 5 genera of zooplankton. Wiyarsih et al, (2019) has argument that the condition of estuary is very influential for plankton abundance especially potential of nitrates and phosphates as main factor to support phytoplankton growth. Sihombing & Aryawati (2013) also notes potential of nutrients such as nitrates and phosphates in the waters have high correlation with abundance of phytoplankton and zooplankton.…”
Section: Plankton Abundance and Diversity In The Donnan Rivermentioning
confidence: 99%
“…Indeks dominansi tersebut menandakan bahwa tidak ada spesies Bacillariophyceae yang mendominasi perairan PPI Tanjung Luar (Odum, 1993dalam Purnamaningtyas et al, 2019. Hal serupa yang dilaporkan oleh Wiyarsih et al, (2019) 3 Ph 7 7 7 7 7 7 4 DO (mg/l) 6 6,2 7 6,8 6,8 6,56…”
Section: Indeks Dominansi Spesiesunclassified
“…Various plankton studies have been carried out in lake waters, both natural and artificial lakes, such as Lake Pondok Lapan (Muhtadi et al 2015), Lake Toba (Rahman et al 2016), Lake Ebony (Pratiwi et al 2018a), Lake Matano (Sulawesty 2019), Lake Maninjau (Sulastri et al 2019). Some research on estuarine and mangrove waters has been widely carried out and reported, such as the Mahakam Delta, East Kalimantan (Effendi et al 2016), Belawan Estuary (Dimenta et al 2018), Segara Anakan, Central Java (Dewi et al 2019;Wiyarsih et al 2019); including bay and coastal waters, such as in Gorontalo Bay (Kadim et al 2018), Sunda Strait (Takarina et al 2019), Banten Bay, Lampung and Jakarta (Sidabutar et al 2016;Damar et al 2020). However, no research has been reported on the dynamics of plankton in tidal lakes in Indonesia.…”
Section: Introductionmentioning
confidence: 99%